Evidence for Disruption of Mg2+ Pair as a Resistance Mechanism Against HIV-1 Integrase Strand Transfer Inhibitors - Machado, Lucas de Almeida; Guimarães, Ana Carolina Ramos (Frontiers in Molecular Biosciences, 2020)
HIV-1 integrase is the enzyme responsible for integrating the viral DNA into the host genome, and is one of the main targets for antiretroviral therapy; however, there are documented cases of resistance against all the currently used integrase strand transfer inhibitors (INSTIs). While some resistance-related mutations occur near the inhibitor’s binding site, the mutation N155H occurs on the opposite side of the drug-interacting Mg2+ ions, thus, not interacting directly with the drug molecules, and currently lacking an explanation for its resistance mechanism. Moreover, mutation N155H and the resistance-related mutation Q148H are mutually exclusive for unknown reasons. In the present study, we use molecular dynamics simulations to understand the impact of the N155H mutation in the HIV-1 integrase structure and dynamics, when alone or in combination with Q148H. Our findings suggest that the Mg2+ ions of the active site adopt different orientations in each of the mutants, causing the catalytic triad residues involved in the ion coordination to adapt their side-chain configurations, completely changing the INSTIs binding site. The change in the ion coordination also seems to affect the flexibility of the terminal viral DNA nucleotide near the active site, potentially impairing the induced-fit mechanism of the drugs. The explanations obtained from our simulations corroborate previous hypotheses drawn from crystallographic studies. The proposed resistance mechanism can also explain the resistance caused by other mutations that take place in the same region of the integrase and help uncover the structural details of other HIV-1 resistance mechanisms.